2006
DOI: 10.4103/0255-0857.29386
|View full text |Cite
|
Sign up to set email alerts
|

In-vitrosusceptibility testing by agar dilution method to determine the minimum inhibitory concentrations of amphotericin B, fluconazole and ketoconazole against ocular fungal isolates

Abstract: Purpose: To standardize in-vitro antifungal susceptibility testing by agar dilution method to find out the minimum inhibitory concentration (MIC) of amphotericin B, fluconazole and ketoconazole on ocular fungal isolates. Methods: A total of 180 ocular fungal isolates (130 filamentous fungi and 50 yeasts) were included. The antifungal drugs such as amphotericin B (0.0625-8 µg/mL), fluconazole (0.2-819.6 µg/mL) and ketoconazole (0.025-6.4 µg/mL) were incorporated in doubling dilutions in the yeast nitrogen base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 18 publications
3
38
2
Order By: Relevance
“…The minimum inhibitory concentration (MIC) of the antifungal were determined by liquid medium microdilution technique according to the protocol described by the National Committee and Clinical Laboratory Standard (NCCLS, 2002 (Thérèse et al, 2006) …”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum inhibitory concentration (MIC) of the antifungal were determined by liquid medium microdilution technique according to the protocol described by the National Committee and Clinical Laboratory Standard (NCCLS, 2002 (Thérèse et al, 2006) …”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…Spectrum of disease is varying from asymptomatic candiduria to clinical sepsis. Several reports showed that the frequency of urinary tract infection due to yeasts has increased during the last decade (Yashavanth et al, 2013). Changes in the clinical severity of candidiasis and the Candida species prevalence profile may be a reflection of immunological changes in HIV positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since discrepancies in CFU (colony forming unit) criteria to diagnose candiduria have not yet been adequately addressed, the following CFU cut-offs were considered in this study: a quantitative culture with a colony count of ≥10,000 CFU/mL of urine was associated with infection while a colony count of <10,000 CFU/mL of urine was associated with colonization (Wise et al, 2000;Kauffman, 2014). Interpretive breakpoints established by the EUCAST (2008) and Thérèse et al (2006) were used. They were as follows: ketoconazole: Sensitive (S) ≤ 0.125 μg/ml, Intermediate (I), 0.25-0.5 μg/ml, Resistant (R), ≥ 1 μg/ml; fluconazole (S) ≤ 8μg/ml, (I), 16-32 μg/ml, (R) ≥ 64 μg/ml; amphotericin B and nystatin (S) ≤ 1μg/ml, (I), 2-4 μg/ml, (R) ≥ 1 μg/ml.…”
Section: Antifungal Susceptibility Testmentioning
confidence: 99%
“…The synthesized compounds were screened for the antibacterial and antifungal activity by using the agar-cup technique in nutrients agar and potato dextrose agar media, respectively [39][40][41][42][43][44][45][46][47][48][49][50]. Ciprofloxacin and gresiofluvin were used as standard drug for the antibacterial and antifungal activity respectively and zone of inhibition of all newly synthesized compounds (IIIa-j) and (IVa-j) was measured against these standard drugs (Table 1 and 2).…”
Section: Biological Activitymentioning
confidence: 99%